Relação entre épocas de semeadura e grupos de maturação de cultivares de soja na viabilidade técnica e econômica do milho safrinha no sul do Brasil - Oligini, Karine Fuschter (2019)
Soybean sowing date and relative maturity group are the most important management tool used by farmers once it plays a major role on the viability of soybean-maize double summer crop succession, especially at the southern of Brazil. Due to it, this study aimed to understand the relationship among these parameters in the agronomic and economic viability of maize as a second summer crop in southern Brazil. The trial was carried out at Dois Vizinhos-PR along the 2016/17 and 2018/19 growing season. Experiment was laid out as a randomized complete block design in a factorial scheme with three replications. Factor A was related to three soybean cultivars (P95R72 RR®, P95R51 RR® and P95Y52 RR® in the 2016/2017 growing seasons being the P95R72 RR® switched for P96Y90 RR® in the 2017/2018) and factor B for three periods of soybean sowing (09/12, 10/01 and 10/15 +3 days variation between years) being maize (P3431VYH) sowing periods a consequence of the soybean cultivars (different cycle and sowing period resulted in nine maize sowing periods). There was interaction between soybean sowing periods and its genotypes for the plant height, thousand grain-weight and grain yield for both years. Soybean cultivars with a maturation cycle between 5.1 and 5.3 sowed in mid- September (12/09) presents better positioning for maize, but worse technical feasibility for the soybean-maize double summer crop in relation to its sowing on the beginning of October, which results in a better yield/risk balance for this succession. Although, soybean cultivar with longer maturity groups (P96Y90 RR®) showed to be a good option for the opening sowing period at mid-September once average yield was of 5972.45 kg ha-1 thus allowing maize to be sown in mid-February, with average yield of 6869.93 kg ha-1 with profitability of 70% for this double crop. Soybean sowing in mid-October (after wheat) results in maize sowing at the end of February (outside of crop zoning), making its cultivation unfeasible. Considering the economic data from the soybean + maize as a second summer crop, the arrangement with greater profitability was soybean P95R51 RR® sown on 09/15 with corn sowed in 01/22 in the first year and in 10/01 with corn sowed in 02/09 in the second year with a profitability index of 49.9 and 29.9 and 63.3 and 15.2% respectively for soybean and corn at the first and second year.